Educating the Brain to Avoid Dementia: Can Mental Exercise Prevent Alzheimer Disease? - Gatz, Margaret (Public Library of Science, 2005)
Physicians often recommend to older adults that they should engage in mentally stimulating activity to reduce the risk of dementia. But is this recommendation based on sound evidence?